Efeitos do exercício aeróbio sobre o acúmulo de gordura visceral em ratos wistar submetidos a um modelo experimental de obesidade - Dantas, Eduardo Miranda (2008)
Objectives: The purpose of this study was to evaluate the effect of the chronic aerobic exercise on body weight gain and visceral fat accumulation in rats raised in small litters as compared to rats raised in normal litters. Additionally the metabolic and hemodynamic characteristics of these groups were also investigated. Methodology: Non-mated female Wistar rats were mated at age of three months with rats of the same age/strain. On the first day of life, the pups were randomly distributed among mothers. On the third day, the size of the offspring was adjusted for three pups in the overfed group (OG) or for 10 pups in the control group (CG). Body weight of the animals was measured weekly. When they completed six weeks of life, 18 animals from OG and 18 from CG were selected for treadmill training, five times a week for nine weeks and the groups were named sedentary overfed (SO), sedentary control (SC), exercised overfed (EO), and exercised control (EC). The intensity of training sessions increased from 10 m/min to 20 m/min, and duration from 10 to 60 minutes. Treadmill inclination was kept at 5º during whole training. At the 8th and 18th weeks of life the rats underwent a maximum treadmill test to evaluate endurance. At the end of the experimental period, the animals were anesthetized to insert a polyethylene catheter (PE50/PE10 tubing) in the femoral artery to measure blood pressure and to collect blood for biochemical evaluation (glicemia, triglycerides, and HDL-cholesterol). After recordings, the animals were euthanized to obtain the weight of some organs (heart, liver and lungs) and of visceral abdominal fat. Results: OG presented greater body weight gain than GC from week 2 of life to the end of the experiment (30+0,85g OG versus 23+0,30g CG, P<0,0001, on the week 2 and 524+3,43g OG versus 469+2,91g CG, P<0,001, on the week 17 of life). At the beginning of the training (week 6 of life) the sedentary and exercised rats did not show significant differences in body weight (210+6,67g SO versus 201+7,77g EO and 188+2,3g SC versus 186+3,3g EC). From the week 10 up to the end of the experiment, there were significant differences of body weight (P<0,05) between SO and EO, but not between SC and EC. There were no significant differences in the hemodynamic and biochemical parameters. In relation to the organ’s weights, there were significant differences in the left ventricle weight to body weight ratio (1,762+0,030mg/g SO versus 1,905+0,040mg/g EO, P<0,01) and kidneys (6,10+0,132mg/g SO versus 6,56+0,135mg/g SC; 6,56+0,132mg/g SC versus 7,32+0,226 mg/g EC; and 6,10+0,135mg/g SO versus 6,92+0,187mg/g EO). The SO group presented greater accumulation of visceral fat in the abdomen as compared to the SC group (31,22g+2,08g versus 21,94+1,76g, P<0,05) and exercise inhibited this visceral fat accumulation in the exercised groups (20,08+2,35g EO versus 13,92+2,42g EC, P < 0,05). Conclusion: Rats fed in a small offspring show a greater body weight gain during the growing period. Part of this body weight gain is due to the accumulation of abdominal fat. Long term aerobic exercise attenuates the body weight gain in these animals by decreasing the visceral fat accumulation.